Dampak Implementasi Model Problem Solving Menggunakan Media Pembelajaran Interaktif pada Mata Pelajaran Sistem Instalasi Refrigerasi - Bayu Abrillian; Dwiprima Elvanny Myori (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This study was conducted to know the impact of implementing the problem-solving model using interactive learning media on the learning outcomes of refrigeration systems and installations of students in class XI of SMK Negeri 1 Sumatera Barat. This research uses quantitative methods in the form of a pre-experimental design with a one-group pretest-posttest design. The participants of this study were XI grade TPTUP students at SMK Negeri 1 Sumatera Barat. This study used instruments in the form of multiple-choice written test questions arranged based on the material and learning objectives to be achieved based on the curriculum. In this study, an instrument test was conducted to determine the validity, reliability, level of difficulty of the questions, and the differentiation of the questions. The data analysis technique used is classical completeness of student learning outcomes and effect size analysis. Based on the results of the research and discussion that has been carried out, it shows that the average value of students’ posttest learning outcomes has increased which can be seen in many students who get scores that reach the criteria for achievement of learning objectives (KKTP) with an achievement presentation of 80.97% which was previously 73.24% and effect size analysis is in the large category. Therefore, the researcher concluded that the implementation of the problem-solving model using interactive learning media in the subject of refrigeration systems and installations at SMK Negeri 1 Sumatera Barat has an impact on improving student learning outcomes.